HNF1A-MODY disease modeling in a dish - a possible role of IL-8 in the increased vascular permeability. (10th June 2022) - Skoczek, D; Stepniewski, J; Kamuda, K; Dulak, J; Kachamakova-Trojanowska, N
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): National Science Centre Maturity Onset Diabetes of the Young (MODY) is an autosomal inherited disease and its most prevalent form is caused by mutations in the hepatocyte nuclear factor 1-alpha (HNF1A). HNF1A-MODY patients often develop vascular complications and have increased incidents of cardiovascular-related death. In our recent work (1), we have established a disease model based on human induced pluripotent stem cells (hiPSCs) derived from a healthy donor and isogenic lines with the mutations either in one of the HNF1A alleles (monoallelic, MAC) or in both of them (biallelic, BAC). After differentiation of these lines toward endothelial cells (hiPSC-ECs), we have shown that HNF1A-mutated hiPSC-ECs have increased permeability after TNFα stimulation. Interleukin 8 (IL-8) could be an important player in this process (2), but its possible role in HNF1A-related increased permeability has not been studied yet. The aim of this study was to evaluate whether increased vascular permeability in HNF1A-mutated hiPSC-ECs could be related to IL-8 production of these cells. Results were based on our previously described isogenic hiPSC-ECs. IL-8 production was assessed with ELISA, proliferation through BrdU incorporation test and apoptosis was evaluated with PO-PRO1/7-AAD kit. There was an increased IL-8 production in BAC line under basic conditions, meaning that these cells present more activated proinflammatory status. After stimulation with TNFα, all hiPSC-ECs increased IL-8 levels, however HNF1A-mutated cells were less efficient. BAC hiPSC-ECs had the lowest IL-8 production after TNFα, meaning that increased vascular permeability in these cells could not be related to IL-8. As IL-8 has also an important role in the proliferation and survival of the ECs (3), we checked whether increased IL-8 production under basic conditions in BAC could have an impact on the proliferation and apoptosis of these cells. The BAC hiPSC-ECs had significantly decreased proliferation compared to both control and MAC lines. Additionally, both HNF1A-mutated lines had an increase in the percentage of the apoptotic cells. After stimulation with TNFα, BAC hiPSC-ECs failed to further increase the percentage of the apoptotic cells, as compared to MAC and control cells. Summarizing, the increased vascular permeability of HNF1A-mutated hiPSC-ECs in response to TNFα could not be attributed to IL-8. The increased IL-8 of BAC hiPSC-ECs under basic conditions did not improve their proliferation or survival capacity. Contrary, these cells showed decreased proliferation and increased percentage of apoptotic cells. Moreover, in response to proinflammatory cytokine, BAC hiPSC-ECs failed to further increase the percentage of the apoptotic cells, which could be related to alterations in the cell cycle of these cells. All these results show that HNF1A-mutated iPSC-ECs have impaired response to TNFα, which may contribute to increased incidence of vascular complications related to HNF1A-MODY.